(untitled) (Contemporary Journal of Social Science Review, 2025)
Social media platforms have played a significant role in which Urdu is being recognized more frequently through different means especially through captions and subtitles that help people to better understand the concept and language the person is trying to convey. Despite this, a serious issue is arising that people are using many incorrect Urdu captions, which frequently cause orthographic errors. These errors are due to the automated transcription system or human errors. Such orthographic inaccuracies lead to many problems that affect the correct or officially accepted Urdu language. These types of errors may cause people to not understand the Urdu language clearly and people would find it difficult to write standard Urdu language in real life after reading those misspelled Urdu subtitles and captions. If these types of errors keep spreading, it could reshape the Urdu language, and people would normalize it and accept it as official over time (Karan, 2020). This research reveals the social as well as linguistic effects of these erroneous Urdu subtitles and shows how people perceive such mistakes and how these mistakes ruin the identity of the Urdu language. Also, how these errors affect the revival of the Urdu language in the future. By doing content analysis of those captions and with the help of surveys of Urdu speakers, this research would lead to uncovering how these inaccuracies in spellings affect people’s better understanding of the Urdu language and portray the wrong image of standard Urdu on social media, and change people’s attitude towards the Urdu language. (Edwards, 2019) The results of this research would contribute to sociolinguistic theory and also provide more knowledge regarding digital reading and writing for better understanding and promote efforts related to orthographic standardization.